Beneficial Microbes (BMs) in organic fertilizer increased the yield of eggplant watered with laundry waste: Exploiting BMs bioremediation and growth promoting potentials - Aban, Jomar L.; Sagun, Analyn V.; Asirot, Jenilyn A. (Asia-Pacific Journal of Science and Technology, 2025)
Beneficial microorganisms (BMs) are naturally occurring soil microbes that are inoculated in organic fertilizers to amplify their abilities to decompose organic matter and make macronutrients readily available to plants. Aside from BMs’ ability to enhance biodegradation, they are also found to bioremediate toxins in the environment. This study was conducted to determine the effect of BMs in organic fertilizer on the vegetative development and yield of eggplants. Using a true experimental design, 210 eggplant seedlings were grown in pots using a randomized complete block design. The average height growth and plant vigor index were highest in eggplants grown in organic fertilizer with beneficial microbes (OFBM) soil media. When laundry waste was used instead of tap water, the eggplants grown in OFBM media produced comparable results, proving potential bioremediating activities by these beneficial microbes. Two significant discoveries were recorded. First, that eggplants grown in OFBM show enhanced growth and fruit production, and second, that the use of laundry waste as irrigation results in comparable yields to those watered with tap water due to the bioremediation capabilities of the BMs. These findings imply that integrating waste materials like laundry water in agricultural practices could promote sustainable farming and soil health by reducing waste while enhancing crop yields. The study recommends practical applications of using laundry waste to irrigate crops grown in OFBM media, promoting ecological sustainability and resource efficiency in agricultural production.